SEEING ANGELS (RU'YAT AL-MALA'IKAT) FOR NON-PROPHETS: A COMPARATIVE ANALYSIS OF THE CONCEPTS OF KASHF AND KARAMAH IN THE THOUGHT OF IBN HAJAR AL-HAITAMI AND AL-GHAZALI - Ali Yusuf Muzaki; Muhammad Fatkhun Niam; Muhammad Syafiiq; Agus Salim; Muh. Fatihuddin; Nur Hanan (Jurnal As-Salam, 2026)
This study examines the discourse on the possibility of seeing angels by non-prophets from the perspectives of hadith and Islamic theology, focusing on the views of Ibn Hajar al-Haitami in Fatawa Hadithiyyah and their comparison with al-Ghazali's Ihya' 'Ulum al-Din. The study is motivated by the emergence of various claims of spiritual experiences in society that require scholarly clarification based on the Islamic intellectual tradition. This research employed a qualitative library research design using a descriptive-comparative approach. Data were collected from primary and secondary sources and analyzed through the stages of description, comparison, and interpretation. The findings indicate that both Ibn Hajar al-Haitami and al-Ghazali affirm that seeing angels by non-prophets is possible (mumkin) and falls within the category of saintly miracles (karamah). However, they differ in their approaches. Ibn Hajar emphasizes divine will within a hadith-theological framework, whereas al-Ghazali highlights inner spiritual purification through the concept of kashf within a Sufi paradigm. The study concludes that such experiences do not contradict Islamic theology as long as they are understood within proper theological boundaries, while providing a scholarly framework for evaluating contemporary spiritual claims in Muslim society.